Strengthening of local vital events registration: lessons learnt from a voluntary sector initiative in a district in southern India - Prem Mony; Kiruba Sankar; Tinku Thomas; Mario Vaz (The World Health Organization, 2011)
PROBLEM: Birth and death registration rates are low in most parts of India. Poor registration rates are due to constraints in both the government system (supply-side) and the general population (demand-side). APPROACH: We strengthened vital event registration at the local level within the existing legal framework by: (i) involving a non-profit organization as an interface between the government and the community; (ii) conducting supply-side interventions such as sensitization workshops for government officials, training for hospital staff and building data-sharing partnerships between stakeholders; (iii) monitoring for vital events by active surveillance through lay-informants; and (iv) conducting demand-side interventions such as publicity campaigns, education of families and assistance with registration. LOCAL SETTING: In the government sector, registration is given low priority and there is an attitude of blaming the victim, ascribing low levels of vital event registration to "cultural reasons/ignorance ". In the community, low registration was due to lack of awareness about the importance of and procedures for registration. RELEVANT CHANGES: This initiative helped improve registration of births and deaths at the subdistrict level. Vital event registration was significantly associated with local equity stratifiers such as gender, socioeconomic status and geography. LESSONS LEARNT: The voluntary sector can interface effectively between the government and the community to strengthen vital registration. With political support from the government, outreach activities can dramatically improve vital event registration rates, especially in disadvantaged populations. The potential relevance of the data and the data collection process to stakeholders at the local level is a critical factor for success.